Long Non-Coding RNA MEG8 Suppresses Hypoxia-Induced Excessive Proliferation, Migration and Inflammation of Vascular Smooth Muscle Cells by Regulation of the miR-195-5p/RECK Axis - Xu, Dexing; Dai, Ruozhu; Chi, Hao; Ge, Wen; Rong, Jingfeng (Frontiers in Molecular Biosciences, 2021)
It has been recognized that rebalancing the abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) helps relieve vascular injury. Presently, we aim to investigate whether long non-coding RNA (lncRNA) maternally expressed 8 (MEG8) plays a role in affecting the excessive proliferation and migration of VSMCs following hypoxia stimulation. A percutaneous transluminal angioplasty balloon dilatation catheter was adopted to establish vascular intimal injury, the levels of MEG8 and miR-195-5p in the carotid artery were tested by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Hypoxia was used to stimulate VSMCs, then the cell counting kit-8 (CCK-8) assay, Transnwell assay, and wound healing assay were conducted to evaluate the proliferation, and migration of VSMCs. The protein levels of RECK (reversion inducing cysteine rich protein with kazal motifs), MMP (matrix metalloproteinase) 3/9/13, COX2 (cytochrome c oxidase subunit II), macrophage inflammatory protein (MIP)-1beta, VCAM-1 (vascular cell adhesion molecule 1), ICAM-1 (intercellular adhesion molecule 1), and HIF-1α (hypoxia inducible factor 1 subunit alpha) were determined by western blot or cellular immunofluorescence. As the data showed, MEG8 was down-regulated in the carotid artery after balloon injury in rats and hypoxia-treated VSMCs, and miR-195-5p was overexpressed. Forced MEG8 overexpression or inhibiting miR-195-5p attenuated hypoxia-promoted cell proliferation and migration of VSMCs. In addition, miR-195-5p up-regulation reversed MEG8-mediated effects. Hypoxia hindered the RECK expression while boosted MMP3/9/13 levels, and the effect was markedly reversed with MEG8 up-regulation or miR-195-5p down-regulation. Mechanistically, MEG8 functioned as a competitive endogenous (ceRNA) by sponging miR-195-5p which targeted RECK. Moreover, the HIF-1α inhibitor PX478 prevented hypoxia-induced proliferation, and migration of VSMCs, upregulated MEG8, and restrained miR-195-5p expression. Overall, lncRNA MEG8 participated in hypoxia-induced excessive proliferation, inflammation and migration of VSMCs through the miR-195-5p/RECK axis.